Therapaws: A partnership between students, staff, and therapy dogs on a university campus - Johinke, Rebecca; Walker, Karen; Kirkaldy, Freia; Sinclair, Caitlyn; Cheng, Wing Lam; Tran, Brian; Williamson, Emerald; White, Grace; Pillai, Sara Sri (International Journal for Students as Partners, 2018)
Partnering with students in action research and asking them how and why they would like to work with staff and other students to improve campus culture and student wellbeing is the cornerstone of this case study. Investment in student mental health and wellbeing is increasingly recognised as a priority in higher education, with novel approaches such as dog therapy programs being introduced in universities around the world. This case study highlights a project where staff and students partner to co-design, co-implement, and co-investigate a mental health and wellbeing program that combines dog therapy with students-as-partners principles. The student-led dog therapy program (Therapaws) provides a practical, evidence-based example of how the principles of SaP can be employed to create an effective intervention into student mental health and wellbeing. This multi-authored case study is also an example of a collaborative writing process—a true partnership.